High-resolution analysis of an erg-margin system from the cretaceous Candeleros Formation (La Buitrera Paleontological Area, Río Negro Province, Argentina): an approach to different scales fluvial-aeolian interactions (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Several studies have emphasized the complexity of the interaction between fluvial and aeolian processes at erg margin settings, and their importance in the resulting geological record. The Cretaceous Candeleros Formation in the “Cañadón de Las Tortugas” site which is located in “La Buitrera Paleontological Area” (Neuquén Basin, Argentina) provides excellent outcrops where the record of a variety of interactions between the aeolian and fluvial processes can be observed. Therefore, the aim of this project was to reconstruct the accumulation systems and the spatial and temporal relations of their associated sedimentary processes. The methodology included the logging of sedimentary sections, a facies and architectural analysis and the identification of the different hierarchies of unconformities. The different architectural elements identified are related both to aeolian and fluvial genesis as mentioned before. The first ones comprise aeolian dune deposits and wet interdune deposits, whilst the second ones are channelized deposits, non-channelized proximal fluvial deposits and non-channelized distal fluvial deposits. These architectural elements were identified in three different evolutive stages of the depositional model made. Hence, the studied interval has a complex pile of overlapping units that represents the contraction/expansion of an erg-margin system as a result of variations of the water table position to climatic conditions. Therefore, this study enhances current understanding of the stratigraphic record of erg margin systems at different time-space scales. This high-resolution study provides a detailed account of the processes that operated in the Kokorkom paleodesert and relevant information for the reconstruction of the accumulation systems in the southern part of the Neuquén Basin during the Late Cretaceous.